1976
DOI: 10.1007/bf01869145
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation and relaxation analysis of monazomycin-induced conductance in black lipid membranes

Abstract: Fluctuation and relaxation analyses were performed on monazomycin-induced conductance of lipid bilayer membranes. With both methods a slow (sec) and a fast (msec) current component are apparent; however, the amplitude of the slow, voltage-dependent process is greater than that of the fast component in the step relaxation experiment and less in the fluctuation experiment. The fluctuation analysis showed principally a rapid voltage-dependent process which appears to be related to the multistate character of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

1978
1978
1984
1984

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…of DECA-induced membrane noise obtained under identical experimental conditions. Thus it can be concluded that the same two processes appear in both relaxation and noise experiments, in agreement with the fluctuation-dissipation theorem (23,24). However, fluctuation experiments are best suited to measure the fast process, whereas relaxation experiments are preferable for measurement of the slow process.…”
supporting
confidence: 78%
“…of DECA-induced membrane noise obtained under identical experimental conditions. Thus it can be concluded that the same two processes appear in both relaxation and noise experiments, in agreement with the fluctuation-dissipation theorem (23,24). However, fluctuation experiments are best suited to measure the fast process, whereas relaxation experiments are preferable for measurement of the slow process.…”
supporting
confidence: 78%
“…According to the fluctuation-dissipation theorem (Onsager, 1931;Kubo, 1957) the correlation time ~' s should be identical with the relaxation time of a voltage-jump current relaxation experiment performed under comparable conditions. Relaxation experiments carried out with monazomycindoped bilayers also show for small changes in the applied voltage (A V~ V << 1) a slow time constant which decreases with increasing voltage (Muller & Finkelstein, 1972a;Moore & Neher, 1976). In contrast to relaxation experiments (Moore & Neher, 1976), the slow process could not be detected anymore at higher voltages by correlation analysis, since the value of oxy~ 9 A decreased beyond a detectable value of about 8 fS.…”
Section: Slow Processmentioning
confidence: 88%
“…In the following, the fitted parameters of C(r) (variances and correlation times) obtained for a multi-pore system will be assigned to single-pore parameters by comparison of the results of the present paper with those obtained from single-pore experiments (Muller & Andersen, 1975;Bamberg & Janko, 1976) and from multi-pore voltage-jump current relaxation experiments (Muller & Finkelstein, 1972a;Moore & Neher, 1976). The results will also be compared with those measured in the presence of the antibiotic alamethicin, for which a similar strong voltage-dependent macroscopic conductance was found (Baumann & Mueller, 1974).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations